Scriptures of the world's religions - edited by James Fieser; John Powers
The fourth edition of Scriptures of the World's Religions brings together many of the world's most influential sacred texts. This text includes chapters on the twelve major religious traditions today, plus two chapters on indigenous religious practices. With comprehensive introductions in each chapter, the selected writings emphasize each religion's founders, central doctrines, and historical development. The translated texts in this collection, many of which were translated specifically for this book, are stylistically clear and up-to-date